2022
DOI: 10.1590/1983-1447.2022.20200218
|View full text |Cite
|
Sign up to set email alerts
|

Elderly victims of violence: family assessment through the Calgary model

Abstract: Objective: To understand the structure, development, and functionality of the family of the elderly victim of violence. Method: Descriptive research with a qualitative approach, based on the Calgary Family Assessment Model. Four elderly people who suffered violence and their family members were assessed at home, from October to November 2019. Data analysis was based on the genogram and ecomap, as proposed in the model. Results: It was found that the members of the four families had low schooling and financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…The consequences of abuse can be especially severe for older people due to the natural aging process, which can lead to functional dependence/disability, poor physical health, cognitive impairment, poor mental health, and low economic capacity [30]. Moreover, the multiple risk factors (e.g., functional dependence, disability, cognitive and physical impairment, drug use, multigenerational households, and income) make it an even more difficult challenge to address [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of abuse can be especially severe for older people due to the natural aging process, which can lead to functional dependence/disability, poor physical health, cognitive impairment, poor mental health, and low economic capacity [30]. Moreover, the multiple risk factors (e.g., functional dependence, disability, cognitive and physical impairment, drug use, multigenerational households, and income) make it an even more difficult challenge to address [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reported a qualitative study design (n � 58) [17,18,21,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and , followed by mixed methods (n � 9) [95][96][97][98][99][100][101][102][103] and quantitative designs (n � 3) [22,104,105]. Data collection methods consisted of semistructured interviews alone (n � 36) [17, 41-44, 46, 48, 52, 53, 56, 58, 59, 61-65, 67, 69, 70, 72, 76, 78-81, 83-85, 88, 89, 92, 93, 104] or interviews combined with focus groups [77,98], surveys [22,95,96,[99][100][101][102][103], participant observations [49,51,…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…First, 24 studies reported an objective of mapping individuals' social, helping or care networks, psychosocial profles, support systems and needs, and social capital [21, 22, 42, 44, 45, 48-50, 52, 55, 57, 64, 65, 68, 73, 78, 84, 93, 95-97, 100, 103], and one paper considered longitudinally the constitution of support networks [66]. Fifteen studies aimed to understand the family structure, function, or organization [56,102], while some were in response to family violence [41,47], addressing chronic and acute mental and physical health conditions [46, 51, 58-60, 70, 74, 79, 101, 105], and natural disasters [54]. Ten studies described participants' use of services and resources, including types of formal social support accessed [63, 69, 72, 81-83, 85, 86, 88, 106].…”
Section: Research Aimsmentioning
confidence: 99%
“…Ela tem por objetivo intervir e auxiliar a família a ultrapassar estes novos desafios, porém se faz necessário dotar os enfermeiros de meios e ferramentas que possibilitem a compreensão das dinâmicas internas da família (HENRIQUES CMG, 2019). É notório que família é a principal rede de apoio para qualquer pessoa, tendo relação sanguínea ou não, a qual é levada para toda a vida (ALARCON MFS, et al, 2021).…”
Section: Introductionunclassified
“…Com o Modelo Calgary de Avaliação Familiar (MCAF) é possível detectar diagnósticos de risco que podem afetar a família do estudo por meio de ecomapas e hemogramas; e aplicar intervenções de acordo com os resultados. O MCAF é frequentemente usado em pacientes com doenças crônicas ou agudas e em diversas situações que necessitam ser investigadas (ALARCON MFS, et al, 2021). O MCAF é composto por 3 categorias onde o modelo estrutural, tem como objetivo observar a estrutura familiar e o convívio com cada componente da família; já desenvolvimento cita a mudança e as situações que a família vem enfrentando; funcional descreve a convivência entre os indivíduos do mesmo núcleo familiar, observando o apoio de cada um (DIAS B, et al, 2020).…”
Section: Introductionunclassified